2016
DOI: 10.1002/chem.201600887
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Palladium‐Catalyzed Alkene Carboamination Reactions for the Synthesis of Cyclic Sulfamides

Abstract: The synthesis of cyclic sulfamides via enantioselective Pd-catalyzed alkene carboamination reactions between N-allyl sulfamides and aryl or alkenyl bromides is described. High levels of asymmetric induction (up to 95:5 er) are achieved using a catalyst composed of Pd2(dba)3 and (S)-Siphos-PE. Deuterium labelling studies indicate the reactions proceed via syn-aminopalladation of the alkene and suggest that control of syn- vs. anti-aminopalladation pathways is important for asymmetric induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Recently,G arlets, Wolfe, and co-workersd escribed the first Pd-catalyzed carboamination reactions of N-allyl sulfamides 42,w hich afforded cyclic sulfamides 43 (Scheme 15). [23] The use of ac atalyst that was derived from [Pd 2 (dba) 3 ]a nd (S)-Siphos-PE afforded the desired products with generally high levels of asymmetric induction. Deuterium-labelling experiments revealed that the reactiono fc ompound 44 proceeded throughasyn-aminopalladationp athway to afford compound 45 with high diastereoselectivity.…”
Section: Asymmetricp D-catalyzed Alkene Carboheterofunctionalization mentioning
confidence: 99%
“…Recently,G arlets, Wolfe, and co-workersd escribed the first Pd-catalyzed carboamination reactions of N-allyl sulfamides 42,w hich afforded cyclic sulfamides 43 (Scheme 15). [23] The use of ac atalyst that was derived from [Pd 2 (dba) 3 ]a nd (S)-Siphos-PE afforded the desired products with generally high levels of asymmetric induction. Deuterium-labelling experiments revealed that the reactiono fc ompound 44 proceeded throughasyn-aminopalladationp athway to afford compound 45 with high diastereoselectivity.…”
Section: Asymmetricp D-catalyzed Alkene Carboheterofunctionalization mentioning
confidence: 99%
“…Our prior studies on the asymmetric synthesis of fivemembered cyclic sulfamides indicated that the reactions proceed via net syn addition to the alkene. 9,12 Given the fact that the transformations described in this manuscript employ similar reaction conditions, and for both five-and six- membered ring-forming reactions the use of the (S)-Siphos-PE catalyst affords the S-enantiomer of the products, we suggest that both transformations proceed through similar mechanisms, which are analogous to the mechanism shown to operate for other alkene carboamination or carboalkoxylation reactions that afford syn-addition products. 13 As shown in Scheme 4, the reaction is initiated by oxidative addition of the aryl halide to Pd(0) to afford 7.…”
Section: Scheme 3 Attempted Cyclization Of Sulfamides Bearing Additiomentioning
confidence: 75%
“…In 2016, our group reported an enantioselective synthesis of five-membered cyclic sulfamides via Pd-catalyzed alkene carboamination reactions between aryl bromides and N-allylsulfamides 1 bearing a N-t-Bu protecting group (Scheme 1, eq 1). 9 These transformations provided the desired products 2 in good chemical yields and good enantioselectivities for a variety of different substrate combinations.…”
mentioning
confidence: 96%
“…Finally, heteroatom tethers, especially sulfonyl, have been also used highly successfully in the past, although again only using stepwise processes. 11 Interestingly, a single example of the use of a boronate tether has also been reported by Cossy and co-workers in the Tsuji–Trost allylation. 12 …”
Section: Introduction: the Tethering Approach For Olefin Functionalizmentioning
confidence: 85%